Psychoeducation Of Anxiety In Parents To Reduce Juvenile Delinquency - Izzah, Lailatul; Hamdi , Raspan; Sarinah , Indah; Ananda Pratiwi, Dea (CV. Pustaka An Nur, 2025)
Parental anxiety about juvenile delinquency is a significant problem, especially in the digital era that worsens the dynamics of the relationship between parents and children. This community service activity aims to provide parents with understanding and skills in managing anxiety through Cognitive Behavioral Therapy (CBT)-based psychoeducation. The target partners are housewives aged 35-50 years who have teenage children (aged 12-18 years) on Jl. Naga Sakti Perum Griya Kenari Indah, with 15-20 participants. The implementation method includes delivering materials, group discussions, question and answer sessions, and ice breaking to build effective communication. Qualitatively, this activity showed an increase in participants' understanding of anxiety, a change in parenting approaches from punishment to empathetic dialogue, and better stress management. Quantitatively, more than 80% of participants actively asked questions and shared experiences, and showed changes in attitudes towards juvenile delinquency. In conclusion, CBT-based psychoeducation is effective in reducing parental anxiety and building more positive parenting patterns, thereby creating more harmonious family relationships.